Comparison of cotinine levels in pregnant women while smoking and when using nicotine replacement therapy - Bowker, Katharine A.; Lewis, Sarah; Coleman, Tim; Vaz, Luis R.; Cooper, Sue (Oxford University Press, 2014)
BACKGROUND: Nicotine replacement therapy (NRT) helps smokers quit smoking, but trials indicate that there is no evidence that it is effective during pregnancy. As metabolism increases during pregnancy, NRT may deliver insufficient nicotine to alleviate withdrawal symptoms. There is mixed evidence as to what levels of cotinine are reached from nicotine exposure during pregnancy while using NRT compared with smoking.